-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathTrivialLang.agda
195 lines (173 loc) · 7.5 KB
/
TrivialLang.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
{-# OPTIONS --safe #-}
module TrivialLang where
open import Relation.Binary.PropositionalEquality as Eq
open Eq.≡-Reasoning
open import Data.Nat.Properties
open import Data.List.Properties
module Preloaded where
open import Data.Nat public
open import Data.List public
data Expr : Set where
const : ℕ → Expr
plus : Expr → Expr → Expr
eval-expr : Expr → ℕ
eval-expr (const n) = n
eval-expr (plus e1 e2) = eval-expr e1 + eval-expr e2
eval-expr-tail' : Expr → ℕ → ℕ
eval-expr-tail' (const n) acc = n + acc
eval-expr-tail' (plus e1 e2) acc = eval-expr-tail' e2 (eval-expr-tail' e1 acc)
eval-expr-tail : Expr → ℕ
eval-expr-tail e = eval-expr-tail' e 0
eval-expr-cont' : {A : Set} → Expr → (ℕ → A) → A
eval-expr-cont' (const n) k = k n
eval-expr-cont' (plus e1 e2) k = eval-expr-cont' e2 λ n2 →
eval-expr-cont' e1 λ n1 → k (n1 + n2)
eval-expr-cont : Expr → ℕ
eval-expr-cont e = eval-expr-cont' e (λ n → n)
data Instr : Set where
push : ℕ → Instr
add : Instr
Prog = List Instr
Stack = List ℕ
run : Prog → Stack → Stack
run [] s = s
run (push n ∷ p) s = run p (n ∷ s)
run (add ∷ p) (a1 ∷ a2 ∷ s) = run p (a1 + a2 ∷ s)
run (add ∷ p) s = run p s
compile : Expr → Prog
compile (const n) = push n ∷ []
compile (plus e1 e2) = compile e1 ++ compile e2 ++ add ∷ []
-- -}
open Preloaded
-- Task 1 - 1. Prove that eval-expr-tail is equivalent to eval-expr.
eval-expr-tail-correct : ∀ e → eval-expr-tail e ≡ eval-expr e
eval-expr-tail-correct (const x) = +-identityʳ x
eval-expr-tail-correct (plus e1 e2) =
begin
eval-expr-tail (plus e1 e2)
≡⟨⟩
eval-expr-tail' (plus e1 e2) 0
≡⟨⟩
eval-expr-tail' e2 (eval-expr-tail' e1 0)
≡⟨ lemma e2 (eval-expr-tail' e1 zero) ⟩
eval-expr-tail' e1 0 + eval-expr-tail' e2 0
≡⟨ cong (λ k → k + eval-expr-tail' e2 0) (eval-expr-tail-correct e1) ⟩
eval-expr e1 + eval-expr-tail' e2 0
≡⟨ cong (λ k → eval-expr e1 + k) (eval-expr-tail-correct e2) ⟩
eval-expr e1 + eval-expr e2
∎
where
lemma : ∀ e acc → eval-expr-tail' e acc ≡ acc + eval-expr-tail' e 0
lemma (const x) acc rewrite +-identityʳ x | +-comm x acc = refl
lemma (plus e1 e2) acc =
begin
eval-expr-tail' e2 (eval-expr-tail' e1 acc)
≡⟨ lemma e2 (eval-expr-tail' e1 acc) ⟩
(eval-expr-tail' e1 acc) + eval-expr-tail' e2 0
≡⟨ cong (λ k → k + eval-expr-tail' e2 0) (lemma e1 acc) ⟩
acc + eval-expr-tail' e1 0 + eval-expr-tail' e2 0
≡⟨ +-assoc acc (eval-expr-tail' e1 zero) (eval-expr-tail' e2 zero) ⟩
acc + (eval-expr-tail' e1 0 + eval-expr-tail' e2 0)
≡⟨
cong (acc +_) (
begin
eval-expr-tail' e1 0 + eval-expr-tail' e2 0
≡˘⟨ lemma e2 (eval-expr-tail' e1 zero) ⟩
eval-expr-tail' e2 (eval-expr-tail' e1 0)
∎
)
⟩
acc + (eval-expr-tail' e2 (eval-expr-tail' e1 0))
≡⟨⟩
acc + eval-expr-tail' e2 (eval-expr-tail' e1 0)
∎
-- Task 1 - 2. Prove that eval-expr-cont is equivalent to eval-expr.
eval-expr-cont-correct : ∀ e → eval-expr-cont e ≡ eval-expr e
eval-expr-cont-correct (const x) = refl
eval-expr-cont-correct (plus e1 e2) =
begin
eval-expr-cont (plus e1 e2)
≡⟨⟩
eval-expr-cont' e2 (λ n2 → eval-expr-cont' e1 (λ n1 → (n1 + n2)))
≡⟨ lemma e2 (λ z → eval-expr-cont' e1 (λ z₁ → z₁ + z)) ⟩
(λ n2 → eval-expr-cont' e1 (λ n1 → (n1 + n2))) (eval-expr-cont' e2 (λ n → n))
≡⟨ lemma e1 (λ z → z + eval-expr-cont' e2 (λ z₁ → z₁)) ⟩
(λ n2 → (λ n1 → (n1 + n2)) (eval-expr-cont' e1 (λ n → n)) ) (eval-expr-cont' e2 (λ n → n))
≡⟨⟩
eval-expr-cont' e1 (λ n → n) + eval-expr-cont' e2 (λ n → n)
≡⟨ cong (λ k → eval-expr-cont' e1 (λ n → n) + k) (eval-expr-cont-correct e2) ⟩
eval-expr-cont' e1 (λ n → n) + eval-expr e2
≡⟨ cong (λ k → k + eval-expr e2) (eval-expr-cont-correct e1) ⟩
eval-expr e1 + eval-expr e2
∎
where
lemma : ∀ e {A} → (accf : ℕ → A) → eval-expr-cont' e accf ≡ accf (eval-expr-cont' e (λ n → n))
lemma (const x) accf = refl
lemma (plus e e₁) accf =
begin
eval-expr-cont' e₁ (λ n2 → eval-expr-cont' e (λ n1 → accf (n1 + n2)))
≡⟨ lemma e₁ (λ n2 → eval-expr-cont' e (λ n1 → accf (n1 + n2))) ⟩
(λ n2 → eval-expr-cont' e (λ n1 → accf (n1 + n2))) (eval-expr-cont' e₁ (λ n → n))
≡⟨ lemma e (λ z → accf (z + eval-expr-cont' e₁ (λ z₁ → z₁))) ⟩
(λ n2 → (λ n1 → accf (n1 + n2)) (eval-expr-cont' e (λ n1 → n1))) (eval-expr-cont' e₁ (λ n → n))
≡⟨⟩
(λ n2 → accf ( (λ n1 → n1 + n2) (eval-expr-cont' e (λ n → n)))) (eval-expr-cont' e₁ (λ n → n))
≡⟨⟩
accf (eval-expr-cont' e (λ n → n) + eval-expr-cont' e₁ (λ n → n))
≡⟨⟩
accf ((λ n1 → n1 + eval-expr-cont' e₁ (λ n → n)) (eval-expr-cont' e (λ n → n)))
≡˘⟨ cong accf (lemma e λ z → z + eval-expr-cont' e₁ (λ z₁ → z₁)) ⟩
accf (eval-expr-cont' e (λ n1 → n1 + eval-expr-cont' e₁ (λ n → n)))
≡⟨⟩
(λ n2 → accf (eval-expr-cont' e (λ n1 → n1 + n2))) (eval-expr-cont' e₁ (λ n → n))
≡⟨⟩
accf ((λ n2 → eval-expr-cont' e (λ n1 → n1 + n2)) (eval-expr-cont' e₁ (λ n → n)))
≡˘⟨ cong accf (lemma e₁ (λ z → eval-expr-cont' e (λ z₁ → z₁ + z))) ⟩
accf (eval-expr-cont' e₁ (λ n2 → eval-expr-cont' e (λ n1 → n1 + n2)))
∎
-- Task 2. Prove that you get the expected result when you compile and run the program.
compile-correct : ∀ e → run (compile e) [] ≡ eval-expr e ∷ []
compile-correct (const x) = refl
compile-correct (plus e1 e2)
=
begin
run (compile e1 ++ compile e2 ++ add ∷ []) []
≡⟨ lemma e1 (compile e2 ++ add ∷ []) [] ⟩
run (compile e2 ++ add ∷ []) (eval-expr e1 ∷ [])
≡⟨ lemma e2 (add ∷ []) (eval-expr e1 ∷ []) ⟩
run (add ∷ []) (eval-expr e2 ∷ eval-expr e1 ∷ [])
≡⟨⟩
run [] (eval-expr e2 + eval-expr e1 ∷ [])
≡⟨⟩
eval-expr e2 + eval-expr e1 ∷ []
≡⟨ cong (_∷ []) (+-comm (eval-expr e2) (eval-expr e1)) ⟩
eval-expr e1 + eval-expr e2 ∷ []
∎
where
4list-assoc : {A : Set} → {a b c d : List A} → (a ++ b ++ c) ++ d ≡ a ++ b ++ c ++ d
4list-assoc {A} {a} {b} {c} {d} =
begin
(a ++ b ++ c) ++ d
≡⟨⟩
(a ++ (b ++ c)) ++ d
≡⟨ ++-assoc a (b ++ c) d ⟩
a ++ ((b ++ c) ++ d)
≡⟨ cong (a ++_) (++-assoc b c d) ⟩
a ++ (b ++ (c ++ d))
∎
lemma : ∀ e x l → run (compile e ++ x) l ≡ run x (eval-expr e ∷ l)
lemma (const x₁) x l = refl
lemma (plus e e₁) x l =
begin
run ((compile e ++ compile e₁ ++ add ∷ []) ++ x) l
≡⟨ cong (λ k → run k l) (4list-assoc {a = compile e} {b = compile e₁} {c = add ∷ []} {d = x}) ⟩
run (compile e ++ compile e₁ ++ add ∷ [] ++ x) l
≡⟨ lemma e (compile e₁ ++ add ∷ x) l ⟩
run (compile e₁ ++ add ∷ [] ++ x) (eval-expr e ∷ l)
≡⟨ lemma e₁ (add ∷ x) (eval-expr e ∷ l) ⟩
run (add ∷ [] ++ x) (eval-expr e₁ ∷ eval-expr e ∷ l)
≡⟨⟩
run x (eval-expr e₁ + eval-expr e ∷ l)
≡⟨ cong (λ k → run x (k ∷ l)) (+-comm (eval-expr e₁) (eval-expr e)) ⟩
run x (eval-expr e + eval-expr e₁ ∷ l)
∎